2022
DOI: 10.1002/anbr.202100159
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Layer‐Specific Ultrastructure and Nanomechanics of Fibrillar Collagen in Human Aorta via Atomic Force Microscopy Testing: Implications on Tissue Mechanics at Macroscopic Scale

Abstract: Soft biological tissues are natural biomaterials with structures that have evolved to perform physiological functions, for example, conferring elasticity while preserving the mechanical integrity of arteries. Furthermore, the mechanical properties of the tissue extracellular matrix (ECM) significantly affect cell behavior and organ function. ECM mechanical properties are strongly affected by collagen ultrastructure, and perturbations in collagen networks can cause tissue mechanical failure. It is thus crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…Fibrillar collagen is a strong and elastic biomaterial arranged in a highly organized hierarchy [ 35 , 36 ]. Type I collagen, the most prevalent of all collagen types, is a coiled helical trimeric molecule made up of repeating sequences of the amino acids Gly-XY, where X and Y are typically found as proline and hydroxyproline [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillar collagen is a strong and elastic biomaterial arranged in a highly organized hierarchy [ 35 , 36 ]. Type I collagen, the most prevalent of all collagen types, is a coiled helical trimeric molecule made up of repeating sequences of the amino acids Gly-XY, where X and Y are typically found as proline and hydroxyproline [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Young’s modulus maps were created using the classic Hertzian approach (Equation (7)) and revealed that Young’s modulus varies between 0.1 KPa to 10 KPa depending on the body area and dermal layer [ 33 ]. Another application is the recording of the ultrastructural and nanomechanical properties of arterial tissues [ 34 ]. The tissue stiffness has been explored using the AFM indentation method.…”
Section: Elastic Half Space Assumption and Standard Young’s Modulus Mapsmentioning
confidence: 99%
“…AFM with large and ultrasharp tips was used to explore tissue stiffness at two scales. Spherical probes for experiments at the micro-scale (tip radius ~2 μm) and sharp probes for experiments at the nanoscale (tip radius ~2 nm) were used [ 34 ]. Hertzian mechanics has also been used for data processing regarding experiments in individual collagen fibrils or collagen fibrils under the influence of external factors [ 3 , 4 ].…”
Section: Elastic Half Space Assumption and Standard Young’s Modulus Mapsmentioning
confidence: 99%
“…The need for an accurate 3D mechanical characterization using various approaches is growing fast, as was shown in [ 18 ], and is considered to be a cutting-edge area of research since the aim is to solve the most important problem in the mechanical characterization of biological samples, which is the current inability to record the mechanical properties at a 3D scale. In other words, existing AFM methods using typical Young’s modulus maps [ 19 , 20 , 21 , 22 , 23 , 24 ] provide a 2D characterization (since they do not take into account the alterations in mechanical properties’ in the 3rd dimension, i.e., as the indentation depth increases, and their results are user dependent).…”
Section: Introductionmentioning
confidence: 99%